Aplicação de análise multicriterial para determinação de áreas prioritárias à recomposição florestal - Nossack, Fábio Ávila [UNESP]; Zimback, Celia Regina Lopes [UNESP]; Silva, Ramon Felipe Bicudo da; Sartori, Anderson Antônio da Conceição [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
Using the Geographic Information System (GIS) and taking into account its capability to analyze spatial data, a database of updated spatial data from the sub-basin of the Descalvado stream, Botucatu, SP, was developed to provide an evaluation and diagnosis of the area concerning land use and the degradation processes therein. Through GIS, priority areas for forest recovery were defined by Multicriteria Evaluation and using the Ordered Weighted Average method. The latter allows the decision maker to define the area to be recovered, facing limitation of resources, among one of the proposed scenarios, or do it in stages. The study showed that there are accelerated erosion processes in the headwaters of the springs of water bodies; there is also fragmentation of native vegetation, especially in hillside areas, and little presence of native vegetation in riparian areas. The application of the multicriteria analysis using the Ordered Weighted Average was important as it systematized and discriminated scenarios of priority for forest recovery.

Utilizando Sistemas de Informação Geográficas (SIG's), dada sua capacidade de análise de dados de natureza espacial, foi confeccionado um banco de dados espacial atualizado da sub-bacia do córrego do Descalvado, município de Botucatu, SP, possibilitando uma avaliação e diagnostico da área quanto à ocupação do território e os processos de degradação que nela ocorrem. Através do SIG foram definidas áreas prioritárias à recomposição florestal por meio da Avaliação Multicritérios, utilizando o método da Média Ponderada Ordenada, que permite que o tomador de decisão decida pela recuperação de uma área, frente a uma limitação de recursos, entre um dos cenários propostos ou o faça por etapas. Conclui-se que há presença de processos erosivos acelerados nas cabeceiras de nascentes dos corpos d ́água; há fragmentação da vegetação nativa, principalmente nas áreas de encosta e pequena presença de vegetação nativa nas zonas ripárias. A aplicação da Análise Multicriterial pelo método da Média Ponderada Ordenada foi importante, pois discriminou e sistematizou os cenários de prioridade para a recomposição florestal.
Application of multicriteria analysis to define priority areas for forest recovery
Keywords: Ordered weighted average; Multicriteria evaluation; Decision making; Environmental recovery; Média ponderada ordenada; Avaliação multicritérios; Tomada de decisão; Recuperação ambiental